PERAN PSIKOLOGI DALAM PENDIDIKAN YANG BERORIENTASI TERHADAP NILAI UNTUK MEWUJUDKAN GENERASI YANG JUJUR DAN AMANAH - Millatus Sa’diyah (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2026)
This study aims to analyze the role of Islamic educational psychology in shaping honest and trustworthy (amanah) character among students. The study employed a qualitative approach through library research by analyzing various relevant literature related to educational psychology, Islamic education, and character development. The findings reveal that Islamic educational psychology plays a significant role in integrating cognitive, affective, and spiritual dimensions within the learning process. The formation of honest and trustworthy character is determined not only by the transfer of knowledge but also by strengthening faith, habituating moral behavior, and creating a learning environment that supports students’ personality development. Pedagogically, these findings emphasize that psychological approaches in Islamic education can create more meaningful learning processes by considering students’ emotional development, self-awareness, and social responsibility. This implies the importance of integrating the values of honesty and trustworthiness into learning strategies, character education models, and teacher–student interactions. This study provides a conceptual contribution to the development of value-based Islamic education, particularly in designing learning processes that are oriented not only toward intellectual achievement but also toward character formation and students’ moral awareness.